Peran Internal Financing dalam Memoderasi Pengaruh Corporate Governance terhadap Leverage pada Perusahaan Manufaktur di Indonesia - Najwasyalita Nur Febrianisa; Hersugondo Hersugondo (Diponegoro Journal of Management, 2026)
Companies seeking long-term growth and development must understand three main elements: corporate governance, capital structure, and financial structure. This study aims to examine the effect of corporate governance on leverage, using internal financing as a moderator and firm size as a control variable. This study was conducted over a five-year period in the manufacturing industry listed on the Indonesia Stock Exchange (IDX). Purposive sampling was used to select 84 out of 344 companies, utilizing secondary data obtained from Bloomberg Terminal and each company’s financial statements. Data testing employed panel data regression and Moderated Regression Analysis (MRA) with a standard error white cross-section (period cluster) approach. Empirical data show that overall corporate governance can affect leverage. Furthermore, the variables AC, MO, IO can directly affect leverage after IF variable is included. In the MRA test, IF variable can moderate and weaken the influence of AC on leverage, and IF is also able to moderate and strengthen the influence of BOD on leverage.